ChatGPT in Academic Writing Classes: Exploring EFL Students’ Perspectives - Tusino, Tusino; Dewi, Puspa; Hati, Mufid Lahiria Permata; Iglesia, Maria Joy C. (JOLLT Journal of Languages and Language Teaching, 2025)
The integration of ChatGPT in English as a Foreign Language (EFL) writing instruction remains a relatively under-researched area, particularly in the Indonesian higher education context. This study explores the dual nature of ChatGPT—as both a pedagogical aid and a potential challenge—for undergraduate English education students at a university in Central Java. Using a qualitative case study design, data were collected from thirty-two participants through a close-response questionnaire to gain insights into their perceptions and experiences. The findings indicate that the use of ChatGPT enhanced students’ writing confidence, time efficiency, and overall quality of written output. Students reported that ChatGPT facilitated idea generation, improved sentence coherence, and served as a valuable tool for self-editing. However, the study also identified several drawbacks, including overreliance on the tool, diminished critical and creative thinking, and concerns about the authenticity and accuracy of AI-generated content. To mitigate these issues, students engaged in peer review, expert consultation, and cross-referencing with credible sources to validate the generated material. The study emphasizes the importance of guiding students toward responsible and reflective use of artificial intelligence in academic writing. Pedagogical implications highlight the need for integrating ethical AI literacy, promoting critical engagement with AI-generated content, and fostering awareness of academic integrity. Ultimately, while ChatGPT presents significant opportunities for enhancing EFL writing pedagogy, its implementation must be thoughtfully managed to ensure it supports, rather than replaces, human cognitive and linguistic development.